Marshall properties of asphalt containing alternative fine aggregates under different ageing conditions - Aletba, Salam Ridha Oleiwi; Abdul Hassan, Norhidayah; Putra Jaya, Ramadhansyah; Aminudin, Eeydzah; Radeef, Hasanain Radhi; Al-Saffar, Zaid Hazim (Suranaree University of Technology, 2023)
Fine aggregate is a main asphalt component, which provides essential effect on the performance of asphalt mixture. Major consumption of aggregate for construction has caused depletion of natural resources and needs for alternative aggregate. Industrial wastes generated from manufacturing processes were laboratory evaluated as alternative fine aggregates in hot mix asphalt with variation in hardness, density and water absorption. Detailed design of the asphalt containing the potential aggregates of garnet and coal bottom ash was prepared and compared with the conventional granite aggregate using Marshall mix design method. The asphalt mixtures were tested for volumetric properties and stability under different ageing conditions. Results showed that fine aggregate has considerably affected the asphalt properties. Garnet improves the asphalt density and stability compared with other fine aggregates under both ageing conditions, thereby suggesting the suitability of garnet as an aggregate in asphalt pavement.